Management of the axilla: has Z0011 had an impact?. (February 2016) - Joyce, D.; Lowery, A.; McGrath-Soo, L.; Downey, E.; Kelly, L.; O'Donoghue, G.; Barry, M.; Hill, A.
Abstract Background Management of axillary disease in breast cancer has evolved significantly over the last two decades with the introduction of SLNB and a trend towards less radical surgery. Data from the American College of Surgeons Oncology Group Z0011 trial proposes that not all patients with positive axillary lymph nodes require completion axillary dissection. Aims The aim of this study was to determine whether there has been a change in practice patterns for axillary management in Ireland since the publication of this 'practice-changing' trial. Methods A review of breast cancers managed in the 12 months prior to publication of Z0011 (pre-Z0011) and comparison with those managed in the following 12 months (post-Z0011) was undertaken in three tertiary referral breast cancer centres. Patients with a positive SLNB were identified, and clinicopathologic data and subsequent management was compared between the two cohorts. Results There were 708 SLNB performed during the study period; 326 pre-Z0011 and 382 post-Z0011. There was no difference in the rate of SLN positivity between the two cohorts: 29.1 % had a positive SLN pre-Z0011 and 29.3 % were positive post-Z0011. There were a significantly lower number of axillary clearances performed in SLN-positive patients in the post-Z0011 period (71.4 %) compared to the pre-Z011 period (93.7 %, p = 0.0022 Chi-square). Of the patients with tumour characteristics meeting the Z0011 inclusion criteria in the initial 12 months of the study, 92.3 % underwent ALND compared with 65.6 % in the final 12 months of the study (p = 0.0006 Chi-square). Conclusions There has been a change in clinical practice since the publication of the Z0011 trial, illustrated by a decrease in the rate of axillary clearance in node-positive breast cancers.